Research Questions and Priorities for Pediatric Tuberculosis: A Survey of Published Systematic Reviews and Meta-Analyses. (7th February 2022) - Vukugah, Thomas Achombwom; Ntoh, Vera Nyibi; Akoku, Derick Akompab; Leonie, Simo; Jacob, Amed
Abstract : Background . Advancing a research agenda designed to meet the specific needs of children is critical to ending pediatric TB epidemic. Systematic reviews are increasingly informing policies in pediatric tuberculosis (TB) care and control. However, there is a paucity of information on pediatric TB research priorities. Methodology . We searched MEDLINE, EMBASE, Web of Science, and the Cochrane Library for systematic reviews and meta-analyses on any aspect related to pediatric TB published between 2015 and 2021. We used the UK Health Research Classification System (HRCS) to help us classify the research questions and priorities. Findings . In total, 29 systematic reviews, with 84 research questions, were included in this review. The four most common research topics in the area of detection were 43.33% screening and diagnosis of TB, 23.33% evaluation of treatments and therapeutic interventions, 13.34% TB etiology and risk factors, and 13.34% prevention of disease and conditions and promotion of well-being. The research priorities focused mainly on evaluating TB diagnosis by improving yield through enhanced in specimen collection or preparation and evaluating of bacteriological TB diagnostic tests. Other topics of future research were developing a treatment for TB in children, assessing the use of IPT in reducing TB-associated morbidity, evaluating the prioritization of an IPT-friendly healthcare environment, and providing additional guidance for the use of isoniazid in the prevention of TB in HIV-infected children. Conclusion . There is a need for more systematic reviews on pediatric TB. The review identified several key priorities for future pediatric TB research mainly in the domain of (1) "Detection, screening and diagnosis, " "Development of Treatments and Therapeutic Interventions, " and "Prevention of Disease and Conditions, and Promotion of Well-Being." These domains are very relevant in the research component of the roadmap towards ending TB in children. It also will serve as an additional action in the WHO End TB strategy.